Walking the Long Road Together - Stilger, Bob (Afternow: When We Cannot See the Future Where Do We Begin?, 2017)
On March 11, 2011, overwhelming and incomprehensible disaster struck the northeast coast of Japan. Life for those in the region would never be the same. This book is about the awakening that follows disaster. About the minutes and months and years that come after now. It is about what happens when we're smacked on the side of the head and open our eyes, startled out of the trance in which we have been living our days. It is about the opportunities always present, often invisible, to create the lives we want, now. AfterNow chronicles the author's journey with the Japanese people over 6 years -- his own story of awakening after plunging into this disaster and the stories from people who found where to take their first step, and the next. It offers the tools and processes and worldview people discovered to create what comes after now. It is built around two big ideas. The first is that after disaster, we find our way forward, together. We come awake, together. Disaster obliterates the past, plunges the present into chaos and cocoons the future. We need each other to see and build the new. The second idea is that we don't have to wait for the tragedy of disaster to make the communities and lives we want. We can engage each other with respect, curiosity and generosity and begin to co-create what we want, now. We live in a period of precipitous, unpredictable change. The book is for those who want to make this time more livable and less insane. In Japan and all over the world, we are living in the messy middle where old forms are falling apart and new possibilities are in early stages. The ground is pulled out from under us on a regular basis. Our work right now is to learn to coexist with the messiness. We need to keep trying things, to keep learning. We need to remain focused on our purpose and follow the braided strand of intention and surrender as we find our way forward. embracing radical uncertainty, showing up as fully as we can each moment, each breath.

The NGO-Academia Interface: Realising the shared potential - Green, Duncan (The Social Realities of Knowledge for Development, 2017)
This edited collection of peer-reviewed papers explores critical challenges faced by organisations and individuals involved in evidence-informed development through a diverse set of case studies and t...

Principles for Monitoring, Evaluation, and Adaptive Management of Environmental Water Regimes - Webb, J. Angus; Watts, Robyn J.; Allan, Catherine; Warner, Andrew T. (Water for the Environment, 2017)
Environmental water is often a contentious investment in the environment that must be delivered under uncertainty regarding the ecological and social benefits they deliver. Adaptive management can be used to facilitate decision making under uncertainty, and use new knowledge and understanding to improve management decisions and outcomes over time. However, there is a perception that adaptive management has failed to deliver improvements in decision making and learning. Monitoring and evaluation are an essential feature of adaptive management. However, past monitoring for river protection and restoration has too often been of insufficient quality to facilitate adaptive learning. Moreover, environmental water represents a class of protection and restoration that is inherently difficult to monitor, and some of the learnings are not evident in part because fragmented assessment, documentation, and reporting of adaptive management can obscure successes. We outline a set of general principles for improving monitoring, evaluation, and adaptive management of environmental water regimes, and provide several examples from Australia and North America. Successful adaptive management depends upon the formation and maintenance of strong partnerships and an appreciation of the importance of individuals in teams. Through such partnerships, it is possible to coordinate monitoring programs over large scales, create programs of requisite simplicity, and use innovative approaches to evaluation. Finally, we note that although adaptive management has occurred in the past, too often it has been poorly documented and reported. The inclusion of reflectors in monitoring and evaluation teams will better capture the lessons learned by individual programs, improving adaptive management into the future.
Keywords: Environmental water management; Knowledge exchange; Legitimacy; implementation challenge

Historical Roots of Dissemination and Implementation Science - Dearing, James W.; Kee, Kerk F. (Dissemination and Implementation Research in Health, 2017)
Research about dissemination and implementation (D&I) is a response to a general acknowledgment that successful, effective practices, programs, and policies resulting from clinical and community trials, demonstration projects, and community-based research as conducted by academicians very often do not affect the services that clinical staff, community service providers, and other practitioners fashion and provide to residents, clients, patients, and populations at risk. In any one societal sector (populated, for example, by planners for health care delivery, or city-level transportation and parkway planners), the state of the science (what researchers collectively know) and the state of the art (what practitioners collectively do) co-exist more or less autonomously, each realm of activity having little effect on the other. In the United States, this situation has been referred to as a “quality chasm” by the U.S. Institute of Medicine.12 Dissemination science is the study of how evidence-based practices, programs, and policies can best be communicated to an interorganizational societal sector of potential adopters and implementers to produce uptake and effective use. For example, public middle school nurses in U.S. southern states can comprise a societal sector. This definition means that dissemination embeds the objectives of both external validity, the replication of positive effects across dissimilar settings and conditions, and scale-up, the replication of positive effects across similar settings and conditions.

Doing Development Differently: Understanding the Landscape and Implications of New Approaches to Governance and Public-sector Reforms - Fritz, Verena (Transformation, Politics and Implementation, 2017)
Seeking to accelerate development, the agencies and individuals involved have regularly advanced new ideas of how external support can function better, deliver more, and achieve greater impact. There has been a particular flourishing of new ideas within the broad field of governance and public-sector reforms in the 2000s. This chapter starts off with a review of the “landscape of new ideas,” focusing on five proposed approaches in particular: political economy analysis (PEA), Problem-Driven Iterative Adaptation (PDIA), Doing Development Differently (DDD), Thinking and Working Politically (TWP), and the “science of delivery.” It sets out the “problem-diagnostic” that underpins each of these

Glossary of Knowledge Management - Serrat, Olivier (Knowledge Solutions: Tools, Methods, and Approaches to Drive Organizational Performance, 2017)
The knowledge management discipline can be cryptic. These Knowledge Solutions define its most common concepts in simple terms.
Keywords: Definitions; Knowledge management; Taxonomy; Terminology

FOCEVAL – Promoting Evaluation Capacities in Costa Rica:: Smart(er) Implementation with Capacity WORKS? - Storm, Sabrina (Transformation, Politics and Implementation, 2017)
The National Monitoring and Evaluation System of Costa Rica and its corresponding laws were established during the 1990s. Since then, the country has endeavored to implement monitoring and evaluation (M&E) activities as part of its public policy framework. Nevertheless, hardly any systematic evaluations had been conducted, and monitoring activities had been reduced mainly to the institutional self-reporting of implementation compliance. Persisting regional disparities and growing levels of inequality among the population raised the level of pressure on the government to present reliable information on the effectiveness of public interventions. Hence, results-oriented evaluations were promoted by some Costa Rican departments as